Achieving high and equitable coverage of adolescent HPV vaccine in Scotland. Issue 1 (28th August 2013) - Sinka, Katy; Kavanagh, Kimberley; Gordon, Ruth; Love, John; Potts, Alison; Donaghy, Martin; Robertson, Chris
Abstract : Background and methods: The national immunisation records of over 220 000 girls offered vaccine in the routine or catch-up programme of the Human papillomavirus (HPV) programme in Scotland were analysed. Descriptive statistics and multilevel modelling were used to determine individual and organisational factors associated with uptake. Age, school year, school denomination, deprivation and, for school-leavers, mode of delivery were explored. Additional aggregate data were used to examine the effect of late uptake of missed doses in the routine vaccination programme. Results: School-based delivery initially achieved over 80% uptake of complete courses in routine and catch-up age groups. Within this context of generally high coverage, there was an association between individual level deprivation and lower uptake, and a decline in in-year course completion over time. However, later uptake of missed doses in the following year substantially decreased these effects. There was no influence on uptake of the type of school (non-denominational/denominational). Vaccination of school-leavers in the catch-up campaign had lower coverage, with 50% starting and 30% completing the course in-year. There was no clear advantage of vaccination through general practice or through Board-run clinics in reaching this group. Conclusions: School-based vaccination can achieve high and equitable uptake of a multidose vaccine in a routine immunisation programme. Sustained high coverage with HPV vaccine across Scotland provides a stable platform for planning future strategies for cervical screening and understanding the impact of the vaccination at a population level.